Low-Grade Oncocytic Tumor: Report of Two Cases of An Emerging Entity in the Spectrum of Oncocytic Renal Neoplasms - Divakar SHARMA; Trupti PAI; Gagan PRAKASH; Sangeeta DESAI; Santosh MENON (Federation of Turkish Pathology Societies, 2022)
Low-grade Oncocytic Tumor (LOT) of kidney is an emerging neoplasm that forms an important differential diagnosis in a spectrum of entities with oncocytic morphology. It has overlapping features with renal oncocytoma and eosinophilic variant of chromophobe renal cell carcinoma, but with distinct clinical, histomorphological and immunohistochemical features. LOT exhibits characteristic low grade oncocytic morphology with a CD117 negative/CK7 positive immunophenotype. Herein, we describe two cases of this emerging entity, LOT, with emphasis on the diagnostic aspects, including the histomorphology, immunoprofile and discussion on the close differentials.